Introductory Note to the Special Issue: Citizenship education, European identities and Young People on the Margins (Revista Lusófona de Educação, 2025)
Citizenship Education is a relatively new area in the curriculum of most European states in its current manifestations, and has been mired in controversies about its purpose, its implementation, and procedures. Earlier, more ideological materialisations were largely in the communist bloc, or the autocracies of Spain, Portugal and Greece. The Federal Republic of Germany (FDR) was a notable exception from 1952 to 1990.The current iterations of Citizenship Education, from the early 1990s, have been accompanied in many states by debates about the nature of citizenship itself, and how citizenship canbe acquired, particularly by means other than by birthplace or parentage (Ross, 2024). Europe, the metropolitan power for a set of empires that encompassed much of the globe, had become a destination for many migrants from these former colonies in the previous 70 or so years, and the consequences of this processcontinue to be contentious in many European states, perhaps particularly for older generations of citizens. Educational policies have been developed in diverse ways, from specifically mandated subjects to cross-curricular approaches (Freires et al., 2024).